2005
DOI: 10.1111/j.0022-202x.2005.23891.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Induces the Generation of Monocyte-Derived Dendritic Cells that Express CD14 but not CD1a

Abstract: The local cytokine environment and the presence of stimulatory signals determine whether monocytes acquire dendritic cell or macrophage characteristics and functions. In this study, we examined the effect of histamine, a prototypic mediator of allergic inflammation, on the granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-4-driven differentiation of monocytes into monocyte-derived dendritic cells (MoDC), which typically showed CD1a+CD14- phenotype. Monocytes from healthy adult dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…By contrast, CD1a – CD14 + skin migratory DC were weak for allogeneic CD4 + T cells with the low expression of HLA‐DR and co‐stimulatory molecules. Recently, we showed that monocytes cultured in the presence of IL‐4, GM‐CSF and histamine differentiated into CD1a – CD14 + DC, in which histamine‐induced endogenous production of IL‐10 by monocytes plays a certain role [12]. 5‐HT also induces CD1a – CD14 + DC, although its effect on monocytic differentiation into CD1a – CD14 + DC was weaker than that of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, CD1a – CD14 + skin migratory DC were weak for allogeneic CD4 + T cells with the low expression of HLA‐DR and co‐stimulatory molecules. Recently, we showed that monocytes cultured in the presence of IL‐4, GM‐CSF and histamine differentiated into CD1a – CD14 + DC, in which histamine‐induced endogenous production of IL‐10 by monocytes plays a certain role [12]. 5‐HT also induces CD1a – CD14 + DC, although its effect on monocytic differentiation into CD1a – CD14 + DC was weaker than that of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that these effects are mediated by soluble protein factors that are excreted from activated platelets. When human monocytes are cultured with IL-4 and GM-CSF in the presence of 5-HT or histamine, they differentiate into CD1aÀCD14+ dendritic cells [51,52]. These DC exhibit enhanced phagocytic activity and cytokine-producing capacity including that for IL-10 but not IL-12, and show a weak allo-stimulatory capacity compared with CD1a+CD14À classical monocyte-derived DC.…”
Section: Platelets Are Involved In the Regulation Of Inflammatory Promentioning
confidence: 99%
“…These cells primarily ingest the pathogens for rapid killing and elimination and further regulate inflammatory reactions by producing proinflammatory or anti-inflammatory cytokines. [74][75][76] Incubation with nanoparticles clearly triggers an activation process, whereas monocyte survival is not influenced. But when considering macrophages, it became obvious that the number of differentiated, viable cells was increased by a-PVA-SPION contact.…”
mentioning
confidence: 99%